The Legality of Digital Evidence in Land Disputes: A Perspective on Civil Procedure Law Reform in the Telematics Era - Rijal Ibnu Sani; Suartini Suartini; Tri Cahya Indra Permana; Ahmad Ahmad; Riri Gusda (Indonesian Journal of Law and Policy Studies, 2023)
The digital transformation of land administration through the implementation of electronic land certificates has significant implications for the evidentiary system in courts. The primary issue arises when conventional civil procedural law is confronted with digital evidence that possesses technical characteristics distinct from physical documents, thereby creating legal uncertainty in the resolution of land disputes. This study aims to analyze the legality and evidentiary strength of electronic land certificates in civil litigation and to formulate an ideal reconstruction of civil procedural law in the digital era. The research employs a normative juridical method with statutory and conceptual approaches. The findings indicate that although electronic land certificates possess legal validity under the Law on Electronic Information and Transactions (ITE Law), their evidentiary strength in court remains fluctuating due to the absence of standardized operational guidelines for judges in verifying the integrity of digital data. The study concludes that civil procedural law reform is necessary to explicitly regulate mechanisms for examining digital evidence, including the obligation to conduct forensic audits and the formal recognition of audit trails. Such reconstruction is essential to ensure substantive legal certainty and to protect landowners from the risk of electronic data manipulation. Through regulatory harmonization between civil law and telematics law, the judicial system can achieve adaptive legal protection in response to the advancement of information technology.